1999
DOI: 10.1161/01.cir.100.16.1744
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic Left Ventricular Mapping in the Porcine Model of Healed Anterior Myocardial Infarction

Abstract: Electroanatomic mapping during sinus rhythm allows accurate 3D characterization of infarct architecture and defines the relationship of electrophysiological and anatomic abnormalities. This technique may prove useful in devising anatomically based strategies for ablation of ventricular tachycardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
177
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(190 citation statements)
references
References 16 publications
11
177
0
2
Order By: Relevance
“…The tissue to electrogram comparison would also be limited by the presence of partial volume effect and other MRI artefacts as well as the relatively lower resolution of the MRI voxels (1 mm 3 ). The unipolar voltages recorded from scar tissue were higher than what is expected from experience in human scars, but similar to voltages recorded from canine scars12 and comparable to values from porcine ventricles 13. This may have been due to the smaller extent of transmural scar and perhaps due to exclusion of noncontact electrograms as the system automatically excluded electrograms from more than 2 mm from the endocardial surface.…”
Section: Study Limitationssupporting
confidence: 62%
See 3 more Smart Citations
“…The tissue to electrogram comparison would also be limited by the presence of partial volume effect and other MRI artefacts as well as the relatively lower resolution of the MRI voxels (1 mm 3 ). The unipolar voltages recorded from scar tissue were higher than what is expected from experience in human scars, but similar to voltages recorded from canine scars12 and comparable to values from porcine ventricles 13. This may have been due to the smaller extent of transmural scar and perhaps due to exclusion of noncontact electrograms as the system automatically excluded electrograms from more than 2 mm from the endocardial surface.…”
Section: Study Limitationssupporting
confidence: 62%
“…Five mongrel dogs weighing 20–25 kg were used for the chronic infarct model 9, 12, 13. The protocol was approved by the Institutional Animal Care and Use Committee at Cedars‐Sinai Medical Center, Los Angeles, CA, USA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20][21][22] Most studies comparing unipolar and bipolar signals are based on animal experiments or computer simulation studies, and only a few clinical studies have been reported. [13][14][15] We evaluated the effects of the recording technique applied on voltage and activation map reconstruction in 4 groups of patients with and without CHD, using the 3D CARTO mapping system.…”
mentioning
confidence: 99%